AKULTURASI BUDAYA PANDALUNGAN DALAM PANDANGAN REMAJA MELENIAL JEMBER - Hery Bambang Cahyono; Rendi Adi Kurniawan; Nando Darwin (MEDIAKOM : Jurnal Ilmu Komunikasi, 2021)
The culture of Pandalungan is still in the process of finding its identity. Two cultures as the main ingredients, namely Madura and Javanese culture continue to complement and complement each other so that the Pandalungan culture has distinctive characteristics from the original culture. When an analogy, Pandalungan culture is like a large pot that accommodates two major cultures, namely Madura and Java, so that it becomes a distinctive culture of the Pandalungan people, especially those in Jember. Melenial adolescents are a generation that is expected to be able to develop, give color and at the same time love Pandalungan culture. Whereas melenial ramaja like ramaja in general are teenagers who are in the process of finding their identity. Often they are proud of the outside culture, forgetting their own culture which is probably better than the outside culture. From the phenomena above, it is appropriate for the researcher to discuss the challenge, how the acculturation of Pandalungan culture in the view of Jember melenial adolescents and what is the obstacle to the acculturation. The theory used is the theory of intercultural communication, namely cultural acculturation. It is a social process when two cultures meet and will give rise to a new culture but it does not eliminate the culture they already have. Furthermore, the method used is descriptive qualitative, while the Jember area is the choice because the Jember area is very Pandalungan compared to other hoof areas. The result is that melenial adolescents do not understand Pandalungan culture and do not pay attention, but in fact they support the growth and development of Pandalungan culture. While the obstacles faced in the development of the Pandalungan culture are 1. there are cultural differences that Madurese are still Madurese and Javanese are also Javanese 2. They do not care about the Pandalungan culture. 3. limited form of Pandalungan culture and 4. Increasing influence of pop culture